2015
DOI: 10.1007/s00595-015-1290-4
|View full text |Cite
|
Sign up to set email alerts
|

A comparison between fentanyl plus celecoxib therapy and epidural anesthesia for postoperative pain management following laparoscopic gastrectomy

Abstract: Purpose To clarify the efficacy of postoperative pain management following laparoscopic gastrectomy (LG), we retrospectively compared pain assessments in patients who received fentanyl plus celecoxib with those who received epidural anesthesia. Results No significant difference in the severity of postoperative pain on postoperative day (POD) 0 or 1 was observed between the two groups. In contrast, pain was significantly lower in Group-FC than Group-E on POD 2, 3, 4, and 7. The total use of rescue pain medicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 32 publications
0
3
0
2
Order By: Relevance
“…Measures that have been reported to assist in the treatment of postoperative pain include inducing local anesthesia, decreasing pneumoperitoneum pressure[3], and administering non-steroidal anti-inflammatory drugs (NSAIDs) and opioids[10]. We found several trials that assessed the effects of local anesthesia in intraperitoneal, subdiaphragmatic, and trocar sites, which significantly decreased postoperative pain scores[11,12].…”
Section: Discussionmentioning
confidence: 99%
“…Measures that have been reported to assist in the treatment of postoperative pain include inducing local anesthesia, decreasing pneumoperitoneum pressure[3], and administering non-steroidal anti-inflammatory drugs (NSAIDs) and opioids[10]. We found several trials that assessed the effects of local anesthesia in intraperitoneal, subdiaphragmatic, and trocar sites, which significantly decreased postoperative pain scores[11,12].…”
Section: Discussionmentioning
confidence: 99%
“…It has also been reported that non-steroidal anti-inflammatory drugs (NSAIDs) exert synergistic analgesic effects when used concomitantly with opioids [20]. We previously reported the efficacy of our new analgesic protocol using celecoxib and fentanyl after laparoscopic gastrectomy [21]. However, to date, there are no reports on the analgesic effects of celecoxib after laparoscopic colorectal surgery.…”
Section: Introductionmentioning
confidence: 93%
“…En esta revisión se incluyeron cinco revisiones sistemáticas (7-11); once estudios de cohorte retrospectiva (1,12-21); tres de cohorte prospectiva (3,22,23); siete ensayos clínicos controlados aleatorizados (24-30); dos ensayos clínicos no aleatorizado (31,32); un reporte de caso (33); y un metaanálisis de ensayos clínicos controlados aleatorizados (34).…”
Section: Calidad De Estudios Y Sesgounclassified
“…La anestesia espinal torácica, al producir un bloqueo selectivo de la inervación simpática cardíaca (T1-T5), produce disminución del efecto adrenérgico, reduciendo la presión arterial, frecuencia y contractibilidad cardíaca, que son los mayores determinantes de la demanda de oxígeno miocárdico durante la intervención quirúrgica. Adicionalmente, el bloqueo produce vasodilatación coronaria y sistémica, aumentando el flujo sanguíneo en las regiones isquémicas del miocardio, y también una reducción en la precarga y poscarga (3,4).…”
Section: Introductionunclassified